Household sharing and commitment: Evidence from panel data on individual expenditures and time use - Jeremy Lise; Ken Yamada (Institute for Fiscal Studies (IFS), 2014)
In this paper, we analyze the nature of intra-household allocations and commitment using unique panel data on individual-specific within-household consumption expenditures and on time used for leisure, market production and home production. Specifically we estimate a dynamic collective model of the household in which husbands and wives care about private consumption, private leisure, and a public good produced in the home with time and market purchased inputs. We find that the household weight on the wife is strongly related to her relative market productivity in the cross-section. Additionally, within households the weight on the wife is related to unpredicted changes in relative wages, but the effect is about half as strong, and only statistically significant for large changes. Our results are consistent with limited commitment within the household: small shocks are fully insured while large shocks provoke a renegotiation.
Keywords: D12; D13; J22; 330; intra-household allocations; dynamic collective model; limited commitment